Bioaccumulation and toxicity of microplastics and pesticides in Fiddler crabs from a ramsar site in the estuary of Guayas river - Villegas, Lipsi (2021)
Pesticides and Microplastics (MPs) pose a major threat to ecosystem functionality and to biodiversity 15 in estuarine ecosystem. In this study, we assessed two objectives. 1) The concentration of organophosphate 16 pesticides (OPs) and MPs in water and sediments from the burrows, and tissues of the fiddler crabs Leptuca 17 festae and Minuca ecuadoriensis. Both species from Isla Santay, a Ramsar site in the estuary of the Guayas 18 River, Ecuador. 2) The effects of the exposure experiment to microplastic (MP) and its interaction with 19 malathion (MLT) in the survival of M. ecuadoriensis and MPs bioaccumulation. MPs concentrations in the burrows were up 660 ± 174.36 items kg-1 wet weight and 26 items L-1 20 in collected sediments and water, 21 respectively. Regarding OPs, water and sediment concentrations were up to 26 times above the United States 22 Environmental Protection Agency (US EPA) thresholds for chronic exposure. The highest abundance of MPs 23 in the tissues was found in the gills. OPs concentrations in tissues were below the detection limits. The results 24 of the exposure experiment showed a higher decrease in the survival in MLT+MP treatment (80%) compared 25 to MLT (20%), MP (0%), and control (8%). The bioaccumulation of MPs was reported in the gills, digestive 26 tract, and hepatopancreas. However, the higher concentration of MPs was reported in the MLT+MP treatment. 27 Because MPs can increase the toxicity of malathion in fiddler crabs, which are chronically exposed to MPs 28 and OPs, they represent suitable bioindicators to monitor Isla Santay and to comprehend the effects of human 29 activities on the coastal environment of Ecuador.